Photocatalytic Hydroalkylation of Trifluoromethyl Alkenes with Gaseous Alkanes in Flow - Nova-Fernández, José L.; Fañanás-Mastral, Martín (Synlett, 2025)
The conversion of light alkanes into value-added products is becoming a field of high interest within the scientific community, as it avoids the use of prefunctionalized alkylating agents. However, the gaseous nature of these reagents, along with their intrinsic inertness due to their high bond-dissociation energies (99–105 kcal·mol–1), have rendered traditional strategies ineffective or lacking in selectivity. The use of flow-chemistry technology has made a tremendous impact in this field, improving the efficiency of multiphasic processes through improved mass transfer and larger interfacial areas. In this work, we report a new flow-chemistry platform for the photocatalytic hydroalkylation of trifluoromethyl alkenes with both isobutane and n-butane. The methodology provides an efficient alternative for the rapid construction of trifluoromethyl alkanes, which are well-known and important bioisosteres of several functional groups.
Keywords: photocatalysis; flow chemistry; HAT photocatalysis; gaseous alkanes; trifluoromethyl alkanes